Final answer:
To find h(8)-f(-7), evaluate h(8) and f(-7), then subtract f(-7) from h(8). The result is -14.
Step-by-step explanation:
To find h(8)-f(-7), we need to first evaluate h(8) and f(-7), and then subtract f(-7) from h(8).
Given that h(x) = |9 - 3x|, we substitute x=8 into the equation to find h(8).
h(8) = |9 - 3(8)| = |-15| = 15
Now, given that f(x) = -4x + 1, we substitute x=-7 into the equation to find f(-7).
f(-7) = -4(-7) + 1 = 29
Finally, we subtract f(-7) from h(8) to find h(8)-f(-7).
h(8)-f(-7) = 15-29 = -14
Question:
Use f(x) = -4x + 1, g(x) = x² - 8x + 21 and h(x) = |9 - 3x|. Find h(8)-f(-7).